Cardiovascular phenotyping of the first mouse model of Sarcoidosis. (25th November 2020) - Bueno Beti, C; Lim, C; Protonotarios, A; Kiss, A; Sheppard, M.N; Szabo, P.L; Behr, E; Hamza, O; Podesser, B; Weichhart, T; Asimaki, A
Abstract: Introduction: Sarcoidosis is a potentially life-threatening, inflammatory, granulomatous disease that affects multiple organs including the heart. Heretofore, its unknown etiology had hindered the creation of experimental models and the understanding of the molecular mechanisms of pathogenesis behind it. Purpose: To extensively phenotype the heart of the first mouse model of sarcoidosis created through deletion of the tuberous sclerosis 2 (Tsc2) gene in the CD11c-positive macrophage population. Methods: Tsc2 fl/fl CD11c Cre+ (Tsc2-KO; n=7) and Tsc2 fl/fl CD11c Cre- (Tsc2-WT; n=7) mice were subjected to echocardiography at 25 weeks of age (woa) to assess myocardial dimensions and function. Hearts of 13 and 25woa animals were subjected to histological and immunological stains to assess tissue changes, subtype inflammatory infiltrates and examine the localization of key proteins shown to be re-distributed in patients. Results: At 13 woa, Tsc2-KO animals show inflammatory infiltrates; subtyped mainly as macrophages as well as evidence of myocyte destruction. At 25 woa, the number of inflammatory cells is significantly higher and there is heavy fibrotic replacement primarily in the septum and trabeculae. Older animals also show giant cells and non-necrotizing granulomas. The hearts show heterogeneous gap junction remodeling known to constitute an arrhythmogenic substrate and lack of immunoreactive signal for the desmosomal protein plakoglobin from the cell-cell junctions just as described in patients. The left ventricular ejection fraction and LV morphology was not significantly different between the two groups (EF: 64±4% in Tsc2-KO vs 64±2% in Tsc2-WT; LV end-systolic diameter: 4.51±0.54 mm in Tsc2-KO vs 4.59±0.29 mm in Tsc2-WT). However, there was a strong trend towards increasing filling pressure (E/e'ratio; 14.24±4.01 vs 12.15±2.54) and mean pulmonary pressure (21±6 vs 18±3 mmHg) in Tsc2-KO mice compared to controls suggesting diastolic dysfunction. Conclusion: Hearts of the Tsc2 fl/fl CD11c Cre+ animals show a phenotype highly reminiscent of cardiac sarcoidosis in patients. We anticipate that this model will be very useful in deciphering molecular mechanisms of pathogenesis as well as testing much-needed mechanism-based therapies. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): British Heart Foundation - PG/18/27/33616